2021
DOI: 10.3389/fmicb.2021.748950
|View full text |Cite
|
Sign up to set email alerts
|

Shelf Life and Simulated Gastrointestinal Tract Survival of Selected Commercial Probiotics During a Simulated Round-Trip Journey to Mars

Abstract: To enhance the gastrointestinal health of astronauts, probiotic microorganisms are being considered for inclusion on long-duration human missions to the Moon and Mars. Here we tested three commercial probiotics—Bifidobacterium longum strain BB536, Lactobacillus acidophilus strain DDS-1, and spores of Bacillus subtilis strain HU58—for their survival to some of the conditions expected to be encountered during a 3-year, round trip voyage to Mars. All probiotics were supplied as freeze-dried cells in capsules at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…It can also tolerate the acidic environment in the digestive tract and heat [77], which enables effective delivery to the gut and enhanced stability during storage and transportation. Fajardo-Cavazos and Nicholson reported that freeze-dried B. subtilis spores in capsules can survive up to 3 years, not only in ambient conditions, but also in a round trip voyage to Mars with the presence of Galactic cosmic radiation and solar particle-event radiations [52]. In addition, B. subtilis is easy to modify genetically [78], which makes it easier to design recombinant spores targeting both the original SARS-CoV-2 and mutant viruses (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can also tolerate the acidic environment in the digestive tract and heat [77], which enables effective delivery to the gut and enhanced stability during storage and transportation. Fajardo-Cavazos and Nicholson reported that freeze-dried B. subtilis spores in capsules can survive up to 3 years, not only in ambient conditions, but also in a round trip voyage to Mars with the presence of Galactic cosmic radiation and solar particle-event radiations [52]. In addition, B. subtilis is easy to modify genetically [78], which makes it easier to design recombinant spores targeting both the original SARS-CoV-2 and mutant viruses (Figure 1).…”
Section: Discussionmentioning
confidence: 99%
“…B. subtilis vaccines also have a lower production cost. Freeze-dried B. subtilis spores in capsules are stable for long-term storage under ambient conditions [52]. Therefore, we believe that oral B. subtilis vaccines could be a potential candidate for the treatment of COVID-19.…”
Section: Introductionmentioning
confidence: 95%
“…can survive aggressive gastric conditions and reach the small intestine in large numbers where they germinate into vegetative form [ 9 ]. Spore-based probiotic formulations have a long shelf life and do not require refrigeration during storage [ 10 , 11 ]. Moreover, Bacillus spp.…”
Section: Introductionmentioning
confidence: 99%
“…The extreme resistance of B. subtilis spores, which guarantees passage through the harsh gut environment without losing characteristics ( 63 ), is the basis for their oral applications as probiotics or as delivery vehicles ( 20 , 24 , 26 29 , 31 , 32 , 60 , 64 68 ). Spores’ direct incorporation into animal feed, circumventing further protection processes, such as encapsulation, together with their simple production and long shelf-life without needing refrigeration ( 51 , 69 ), are also attractive characteristics from the industrial point of view ( 70 ). Adding to this “needle-free” and “refrigeration-free” potential, B. subtilis spores adjuvant properties ( 18 , 19 , 71 73 ) and contribution to GALT (gut associated lymphoid tissue) development ( 67 , 74 – 76 ), increases their potential as oral delivery systems of antigens.…”
Section: Discussionmentioning
confidence: 99%